PEMBERDAYAAN MASYARAKAT SEBAGAI UPAYA PEMANFAATAN INSENERATOR DALAM MENGELOLAH SAMPAH ANORGANIK - Mariene Wiwin Dolang; Zulfikar Lating; Abd. Rijali Lapodi; M. Taufan Umasugi (Politeknik Negeri Sriwijaya, 2021)
Garbage is one of the factors causing environmental damage in Indonesia. Although many people understand the consequences of piling up garbage, in fact the waste problem has not become a top priority to be solved. Waste will increase along with the increase in population and the level of public consumption and other activities. The reality that is happening now is only the